ALLIANCE FORGED - Griffin, Kylie. (Berkley Sensation, 2012)
There is no mercy in the demon realm. No escape. In this place of desperation and conflict, anyone who is not purebred is virtually powerless. Until a blind priestess lays claim to a half-breed warrior, body, and soul.